DESCRIPTION OF STUDENTS' MENTAL MODELS ON BUFFER SOLUTION MATERIALS USING FOUR-TIER DIAGNOSTIC TESTS - Ramadhani, Fajri; Azra, Fajriah (FKIP USK, 2024)
Mental models are very important to know because they can describe the level of students' understanding of chemical phenomena related to certain materials, one of which is a buffer solution that emphasizes the interconnection understanding of the three levels of chemical representation. This study aims to describe the mental model of students in buffer solution materials. The research method used is quantitative descriptive. The sampling technique was purposive sampling, with a sample of 35 students. The research instruments used were a four-tier multiple choice diagnostic test based on mulltire, chemical presentations, and interviews.The results showed that the mental models of students on the buffer solution material were diverse, namely: Scientific Model with a percentage of 18.05%, Synthesis-Partial Understanding A of 5.35%, Synthesis-Partial Understanding B of 32.34%, Synthesis-Misconception of 26.27%, and Initial Model of 21.54%. The percentage of agreement between the test answers and the interview answers was 75% which showed that the answers given in the test and the interview were correct from the students' own understanding.